2013
DOI: 10.1056/nejmsa1211128
|View full text |Cite
|
Sign up to set email alerts
|

21st-Century Hazards of Smoking and Benefits of Cessation in the United States

Abstract: Smokers lose at least one decade of life expectancy, as compared with those who have never smoked. Cessation before the age of 40 years reduces the risk of death associated with continued smoking by about 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
808
3
20

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,509 publications
(850 citation statements)
references
References 15 publications
19
808
3
20
Order By: Relevance
“…Given this, it appears unlikely that varenicline would increase cardiovascular risk through its activation of nAchRs, and if possible, the occurrence of such events would be extremely rare. This potential risk must also be considered in the context of the exceptional role of quitting smoking in reducing cardiovascular risk 59, 60. The cardiovascular benefits of varenicline as an efficacious smoking‐cessation pharmacotherapy61 far outweigh a speculative and extremely small potential increase in cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, it appears unlikely that varenicline would increase cardiovascular risk through its activation of nAchRs, and if possible, the occurrence of such events would be extremely rare. This potential risk must also be considered in the context of the exceptional role of quitting smoking in reducing cardiovascular risk 59, 60. The cardiovascular benefits of varenicline as an efficacious smoking‐cessation pharmacotherapy61 far outweigh a speculative and extremely small potential increase in cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding and preventing or reversing the escalation and entrenchment of cigarette smoking in the young adult years is critically important to reducing smoking's long-term health toll (Doll et al 2004(Doll et al , 2005Jha et al 2013;Pirie et al 2013; U.S. Department of Health and Human Services 2014). However, current tobacco control efforts may be missing the mark when one considers the complexity of patterns of young adult tobacco use, including the phenomenon of initiation starting after age 18.…”
Section: Prevescalation As a Research Gap And An Intervention Opportumentioning
confidence: 99%
“…28 Among HIV patients, quitting smoking also appears to convey substantial health benefits. For example, Lifson et al 26 reported that mortality among HIV patients in their sample was significantly higher throughout the follow-up period for current smokers than for former smokers.…”
Section: Health Benefits Of Quitting Smokingmentioning
confidence: 99%